2016
DOI: 10.1159/000447130
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes after Early Neurological Deterioration and Transitory Deterioration in Acute Ischemic Stroke Patients

Abstract: Background and Purpose: Early neurological deterioration (END) occurs in 10-40% of acute ischemic stroke (AIS) patients and has been associated with worse outcome. Recent improvements in treatment may have reduced the prevalence of END. A single early control or repeated observations have been applied to detect END close to occurrence, in order to improve the poor outcome associated with END, as clinical interventions may still be effective. Deterioration detected through repeated observations may be transitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 31 publications
3
26
1
Order By: Relevance
“…Our study demonstrated that END was associated with symptomatic hemorrhage and hernia within 7 days and was also associated with poor outcome at 3 months. Similar findings have been consistently reported in previous studies (10,18). There is no significant correlation between extensive brainstem infarction and END.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our study demonstrated that END was associated with symptomatic hemorrhage and hernia within 7 days and was also associated with poor outcome at 3 months. Similar findings have been consistently reported in previous studies (10,18). There is no significant correlation between extensive brainstem infarction and END.…”
Section: Discussionsupporting
confidence: 92%
“…According to different severity thresholds and the time scales between assessments, the incidence of END varies widely from study to study. The typical definition of END (8,9) is an increase ≥4 points in the National Institutes of Health Stroke Scale (NIHSS) or death within the first 24 h after stroke, and END affects stroke patients' long-term outcomes (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…This is important as early neurologic worsening after stroke has been repeatedly demonstrated to affect longer-term outcome, most recently in an analysis of 368 patients who demonstrated a 35 times increased odds of death or dependency if they demonstrated early neurologic worsening. 32 Different from prior studies, we did not see a high rate of transient neurologic fluctuation in this cohort, as previously reported. 2 Thus, our study provides essential markers to allow us to address persistent questions specific to the relationship between fluid volume and outcomes after stroke.…”
Section: Figure Change In Nih Stroke Scale (Nihss) Score Between Hospcontrasting
confidence: 99%
“…Some previous studies have shown that delirium duration is associated with worse disability scores at 12 months posthospitalization in critically ill adults 26 but, to our knowledge, no previous prospective cohort studies in the ICU have suggested an association between early acute brain dysfunction and posthospital physical disability outcomes in critically ill older adults in stroke survivors, both delirium and acute brain dysfunction have been previously shown to be an important predictor of physical disability outcomes. 27,28 A strong association between early brain dysfunction in critically ill adults and posthospital physical disability would be consistent with the emerging literature in geriatrics that cognitive function is intricately linked to mobility and physical disability. 29,30 In a clinical trial of early exercise and mobilization in a cohort of adults who were functionally independent prior to enrollment, the mobilization intervention was associated with shorter duration of delirium and improvement in functional outcomes which is consistent with the interconnections between physical and cognitive outcomes in critically ill adults.…”
Section: Discussionsupporting
confidence: 77%